African food systems transformation and the post-Malabo agenda - Ulimwengu, John M.; Kwofie, Ebenezer M.; Collins, Julia (AKADEMIYA2063, 2023)
This year marks 20 years of implementing the Comprehensive Africa Agriculture Development Programme (CAADP), which was broadened under the 2014 Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods. The 2023 Annual Trends and Outlook Report generates evidence on the implementation of the CAADP/Malabo agenda and thus contributes to the design of the post-Malabo phase of CAADP implementation. The report assesses the current state of Africa's food systems, explores strategic issues related to food systems transformation, and reflects on necessary methodologies and approaches to provide a better understanding of key challenges and necessary actions to accelerate transformation.